Aerodynamic data generation and design support for solar UAV : CFD for aircraft loads - Muhammad Fursham Mohd Zubir (2014)
The Solar Unmanned Aerial Vehicle (UAV) project was initiated by Defence Science Organization (DSO) National Laboratories, Singapore, in 2011 to develop a perpetual flying platform for surveillance and other missions. Currently in the 3rd year of this assignment, final year undergraduates will look into the detailed design phase of the project. The characteristics of the UAV are studied such that the finer details of the design are finalized before embarking on the next phase of the project. Computational Fluid Dynamics (CFD) analysis is carried out in this project. Prior to conducting the analysis, theoretical aspects of both aerodynamics and CFD will be looked into that is important for this project. This is explained in further detail in chapter 2. Two different types of simulations are carried in this project. The first simulation is the simulation of airfoils with deflected flaps based on the Solar UAV configurations carried out to obtain hinge moment of the control surfaces. Validation studies are conducted for the airfoils with and without deflected flaps. This is to ensure that the CFD codes used capture the aerodynamic characteristics of the airfoils as seen in experimental studies. The suitability of the simulation is based on the validation studies. The simulation and results are explained in further details in chapter 3.2. The second simulation is the simulation of the Solar UAV wing. Validation studies of the airfoil of the wing are again conducted due to the different CFD solvers. Once validated, the simulation of the Solar UAV wing is conducted. The simulation and results are explained in further details in chapter 3.3.